A New Era in Cardiac Rehabilitation Delivery: Research Gaps, Questions, Strategies, and Priorities. Issue 3 (17th January 2023) - Beatty, Alexis L.; Beckie, Theresa M.; Dodson, John; Goldstein, Carly M.; Hughes, Joel W.; Kraus, William E.; Martin, Seth S.; Olson, Thomas P.; Pack, Quinn R.; Stolp, Haley; Thomas, Randal J.; Wu, Wen-Chih; et al.
Abstract : Cardiac rehabilitation (CR) is a guideline-recommended, multidisciplinary program of exercise training, risk factor management, and psychosocial counseling for people with cardiovascular disease (CVD) that is beneficial but underused and with substantial disparities in referral, access, and participation. The emergence of new virtual and remote delivery models has the potential to improve access to and participation in CR and ultimately improve outcomes for people with CVD. Although data suggest that new delivery models for CR have safety and efficacy similar to traditional in-person CR, questions remain regarding which participants are most likely to benefit from these models, how and where such programs should be delivered, and their effect on outcomes in diverse populations. In this review, we describe important gaps in evidence, identify relevant research questions, and propose strategies for addressing them. We highlight 4 research priorities: (1) including diverse populations in all CR research; (2) leveraging implementation methodologies to enhance equitable delivery of CR; (3) clarifying which populations are most likely to benefit from virtual and remote CR; and (4) comparing traditional in-person CR with virtual and remote CR in diverse populations using multicenter studies of important clinical, psychosocial, and cost-effectiveness outcomes that are relevant to patients, caregivers, providers, health systems, and payors. By framing these important questions, we hope to advance toward a goal of delivering high-quality CR to as many people as possible to improve outcomes in those with CVD.